2004
DOI: 10.1158/0008-5472.can-04-0752
|View full text |Cite
|
Sign up to set email alerts
|

Peritumor Lymphatics Induced by Vascular Endothelial Growth Factor-C Exhibit Abnormal Function

Abstract: Vascular endothelial growth factor (VEGF)-C is known to induce hyperplasia in normal murine lymphatics and in peritumor lymphatics. Here, we examine the function of these hyperplastic peritumor lymphatics. Microlymphangiography of B16F10 melanomas growing in the murine dorsal skinfold chamber showed that the number of functional, draining lymphatics in the peritumor tissue of VEGF-C-overexpressing tumors was significantly greater than that in mock-transduced tumors (9.5 ؎ 1.0 versus 6.3 ؎ 0.4; n ‫؍‬ 6; P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
104
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 16 publications
11
104
0
6
Order By: Relevance
“…Although lymphangiogenesis and vessel dilation are thought to increase the delivery of lymph to the draining lymph node, a decrease in drainage has also been observed during inflammation and surrounding some cancers (1,2,7). Whether reductions in collecting lymphatic function can affect subsequent immune response by limiting entry of antigen/dendritic cells (DCs) into the draining lymph node (LN) is not known.…”
mentioning
confidence: 99%
“…Although lymphangiogenesis and vessel dilation are thought to increase the delivery of lymph to the draining lymph node, a decrease in drainage has also been observed during inflammation and surrounding some cancers (1,2,7). Whether reductions in collecting lymphatic function can affect subsequent immune response by limiting entry of antigen/dendritic cells (DCs) into the draining lymph node (LN) is not known.…”
mentioning
confidence: 99%
“…101,102 Abnormal multidirectional flow has been observed in lymphatic vessels draining VEGF-C-overexpressing melanomas implanted in dorsal back skin of mice, suggesting insufficient function of lymphatic valves in that model. 65,90 However, valve function in tumor draining lymphatic vessels may not be insufficient in all tumors, as we have observed functional lymphatic valves by in vivo imaging of lymphatic vessels in footpad melanoma and subcutaneous breast cancer models (Proulx S et al, unpublished data). Upon progression, the arrival of metastatic cells into the lymph node may block the lymphatic sinuses, decreasing fluid flow from the tumor.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 77%
“…89 Some imaging studies have shown that intratumorally injected tracers may be deposited in tumors instead of being cleared by lymphatic drainage. 20,90 A high interstitial pressure within tumors may cause intratumoral vessels to collapse to a non-functional state. 91 Thus, the lymphatic vessels observed inside a tumor, are not necessarily functional with regard to fluid drainage or transport of tumor cells, at least in some experimental models.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%
“…In addition, individual necrotic cell death can be detected by the use of propidium-iodide (Harris et al, 1997), whereas apoptotic cells can be identifi ed by nuclear condensation, margination and fragmentation following local bisbenzimide staining (Vollmar et al, 2001). Besides conventional epi-illumination fl uorescence microscopy, imaging in the dorsal skinfold chamber model has increasingly been performed in recent years by means of confocal microscopy techniques (Isaka et al, 2004;Makale, 2007;Strieth et al, 2008). Using a pinhole aperture for point illumination, single-photon laser-scanning microscopy allows the detection of light from a specifi c volume within the plane of focus, so that the resultant image is comparatively free of scattered light and attendant blurring (Makale, 2007).…”
Section: Mw Laschke Et Almentioning
confidence: 99%
“…Authors: In the past, most studies in the dorsal skinfold chamber model have been performed by means of epiillumination fl uorescence microscopy. However, in recent years confocal microscopy techniques have increasingly gained in importance when using this model (Isaka et al, 2004;Makale, 2007;Strieth et al, 2008, text references), because the obtained microscopic images exhibit an improved optical resolution and contrast. Moreover, it is possible to concatenate individual optical sections to create a three-dimensional reconstruction of the object of interest.…”
Section: Reviewer IIImentioning
confidence: 99%